Syngas Production From the Reforming of Typical Biogas Compositions in an Inert Porous Media Reactor - Guerrero, Fabián; Espinoza, Lorena; Ripoll, Nicolas; Lisbona, Pilar; Arauzo, Inmaculada; Toledo, Mario (Frontiers in Chemistry, 2020)
Syngas production by inert porous media combustion of rich biogas-air mixtures was studied experimentally, focusing in carbon dioxide utilization and process efficiency. Different gas mixtures of natural gas (NG) and carbon dioxide, which simulated a typical biogas composition of 100:0, 70:30, 55:45 and 40:60 (CH4:CO2) were comparatively analyzed considering combustion waves temperatures and velocities, and chemical concentrations products, at high equivalence ratios of φ = 1.5 and φ = 2.0. Different CO2 concentrations on biogas composition showed higher H2 productions than on pure methane (100:0), mainly due to CO2 reforming reactions. Also syngas production, hydrogen yields and process efficiency by means of biogas filtration combustion was higher than under methane filtration combustion. Results of the thermochemical conversion of biogas shows an alternative and promising non-catalytic technique to CO2.